Here's one more thing I want to point out...  This takes us back to when we graphed lines in this form:

y = mx + b

When we let  x = 0, we get the y-intercept (where the graph crosses the y-axis).

y = m ( 0 ) + b  which gives  y = b  and b is the y-intercept

We can do the same thing on these!

Check out the first guy we did:

y = 3x^2 - 1

Let  x = 0

y = 3 x^2 - 1 ... y = 3 ( 0 )^2 -1  which gives  y = -1

The graph of y = 3 x^2 -1 showing that the y-intercept is y = -1

Here's the second one we did:

y = -2x^2 - 4x +1

Let  x = 0

y = -2x^2 - 4x + 1   let x = 0  which gives  y = 1

y = -2x^2 - 4x + 1  showing that the y-intercept is y = 1

 
Once you get the idea, you can get the y-intercept just by glancing!

10-graphing-parabolas-39.gif

 

10-graphing-parabolas-40.gif